2021
DOI: 10.3390/membranes11120984
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Metal Homeostasis in Plants: A New View on the Synergistic Regulation Pathway of Membrane Proteins, Lipids and Metal Ions

Abstract: Heavy metal stress (HMS) is one of the most destructive abiotic stresses which seriously affects the growth and development of plants. Recent studies have shown significant progress in understanding the molecular mechanisms underlying plant tolerance to HMS. In general, three core signals are involved in plants’ responses to HMS; these are mitogen-activated protein kinase (MAPK), calcium, and hormonal (abscisic acid) signals. In addition to these signal components, other regulatory factors, such as microRNAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 251 publications
(198 reference statements)
0
3
0
Order By: Relevance
“…In Cucurbits, all HMA proteins were predicted to localize within the cell membrane. Membrane proteins play a vital role in regulating plant responses to heavy metal stress, as they facilitate the transport of metals across membranes, thereby contributing to metal homeostasis and detoxification processes [54]. Expression of CsHMA3 and CsHMA4 was found to confer tolerance to Cd and Zn with metal efflux tolerance and accumulation of Cd and Pb through sequestration, proving to be part of the Zn/Co/Cd/Pb clade and suggesting its role in plant translocation from the plasma membrane and bioaccumulation of these metals into the vacuoles [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cucurbits, all HMA proteins were predicted to localize within the cell membrane. Membrane proteins play a vital role in regulating plant responses to heavy metal stress, as they facilitate the transport of metals across membranes, thereby contributing to metal homeostasis and detoxification processes [54]. Expression of CsHMA3 and CsHMA4 was found to confer tolerance to Cd and Zn with metal efflux tolerance and accumulation of Cd and Pb through sequestration, proving to be part of the Zn/Co/Cd/Pb clade and suggesting its role in plant translocation from the plasma membrane and bioaccumulation of these metals into the vacuoles [34].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, previous studies have also reported the participation of non-elucidated transporters for arsenic in Pteris vitatta when treated with a mix of Ag-As due to the inhibition of the entrance, translocation, and the enhancement of As tolerance when Ag and As are supplemented simultaneously; it is known that Ag transport and homeostasis across plant tissues are mediated via HMA proteins from the Cu/Ag clade [67,68]. However, metal homeostasis in plants must be regulated using several complex processes [54], and the collaboration of transporters in different tissues may play an important role in plant metal distribution [19].…”
Section: Discussionmentioning
confidence: 99%
“…Natural resistanceassociated macrophage proteins (NRAMP), Metal tolerance proteins (MTP), and heavy metal ATPases (HMA) are actively involved in metal transport. These transporters collectively contribute to effectively regulating plant metal ion levels, highlighting the complexity and cooperation in maintaining metal homeostasis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Natural resistance-associated macrophage proteins (NRAMP), Metal tolerance proteins (MTP), and heavy metal ATPases (HMA) are actively involved in metal transport. These transporters collectively contribute to effectively regulating plant metal ion levels, highlighting the complexity and cooperation in maintaining metal homeostasis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%